Human-based complex in vitro models: their promise and potential for rare disease therapeutics - Parvatam, Surat; Pistollato, Francesca; Marshall, Lindsay J.; Furtmann, Fabia; Jahagirdar, Devashree; Chakraborty Choudhury, Mohua; Mohanty, Sujata; Mittal, Harshita; Meganathan, Saveetha; Mishra, Rakesh (Frontiers in Cell and Developmental Biology, 2025)
Rare diseases affect a small percentage of an individual country’s population; however, with over 7,000 in total, rare diseases represent a significant disease burden impacting up to 10% of the world’s population. Despite this, there are no approved treatments for almost 95% of rare diseases, and the existing treatments are cost-intensive for the patients. More than 70% of rare diseases are genetic in nature, with patient-specific mutations. This calls for the need to have personalised and patient-specific preclinical models that can lead to effective, speedy, and affordable therapeutic options. Complex in vitro models (CIVMs), including those using induced pluripotent stem cells (iPSCs), organoids, and organs-on-chips are emerging as powerful human-based pre-clinical systems with the capacity to provide efficacy data enabling drugs to move into clinical trials. In this narrative review, we discuss how CIVMs are providing insights into biomedical research on rare diseases. We also discuss how these systems are being used in clinical trials to develop efficacy models for rare diseases. Finally, we propose recommendations on how human relevant CIVMs could be leveraged to increase translatability of basic, applied and nonclinical research outcomes in the field of rare disease therapeutics in developed as well as middle-and low-income countries.